Concrete apartment tower in Los Angeles reimagined in mass timber. (15th July 2018) - Timmers, Matthew; Tsay Jacobs, Andrew
Graphical abstract: Highlights: Mass timber is a viable structural material for high-rise buildings. The timber tower has half the mass and half the stiffness of the concrete tower. Mass timber has the structural capacity required for high seismic zones. Abstract: This study explores the seismic performance advantages and disadvantages of mass timber construction over reinforced concrete construction for high-rise buildings in high seismic regions. In a side-by-side comparison of a 20-story reinforced concrete tower and a corresponding mass timber tower, the timber tower is demonstrated to have roughly half the mass and twice the flexibility of the reinforced concrete tower. Building code minimum for acceleration and maximum for drift govern the lateral design of the theoretical mass timber tower, whereas code minimum acceleration and strength govern the reinforced concrete tower. The study demonstrates that mass timber provides a viable alternative to reinforced concrete construction in high seismic regions.